The Degree to which Teachers of the First Three Grades Possess Effective Teaching Skills from the Point of View of Principals in Ain Al-Basha District in Jordan - Hyasat, Ruba Yasser; Abu Sneina, Odeh AbdelGawad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to reveal The Degree to Which Teachers of the First Three Grades Possess Effective Teaching Skills from the Point of View of Principals in Ain Al-Basha District in Jordan. To achieve the study aim, the analytical descriptive approach has been used according to the variables (experience, qualification, sector). The study population consisted of the female Directors in Ain Al-Basha Province for the 2021/2022 year, the study sample was selected by the random sample method and consisted of (56) female directors working in the Ain Al-Basha Directorate (35) female principals from private schools and (21) female principals from among government directors, and to achieve the objective of the study, a two-part questionnaire was prepared. The results showed that the degree to which the teachers of the first three grades possess the planning skill (total), came to a large degree, as the arithmetic mean of the school principals’ responses to the field of planning skill was (4.11), and that the degree to which the first three grades teachers possessed effective teaching skills were General (total), came to a large degree, as the arithmetic mean of the school principals’ responses to the questionnaire as a whole was (4.14), The study recommended conducting more studies on the subject using larger samples, using more variables, and holding courses for effective teaching skills for teachers who hold a bachelor's degree.
Keywords: effective skills; the first three grades